Youth Employment and Skills Development in The Gambia - Lahire, Nathalie; Johanson, Richard; Wilcox, Ryoko Tomita (World Bank, 2012)
Despite substantial improvements in access to basic education and steady economic growth, The Gambia still faces considerable challenges in respect to reducing poverty. As the result of its narrow economic base and its reduced internal market, the country will continue to rely heavily on the productivity of its citizens to reverse the cycle that keeps families in poverty generation after generation. Poverty reduction is a complex equation that involves improvements in job creation, especially for high-skilled and productive employment, as well as improvements in human capital levels to ensure that citizens are able to take advantage of employment opportunities. Currently, however, low human capital levels greatly limit the productivity and employment outcomes of the population, as evidenced by the fact that a majority continues to work in subsistence agriculture, especially in rural areas. Nearly 60 percent of the poor in The Gambia are under the age of 20 years. Youth face significant challenges with respect to employment outcomes, such as a very difficult transition from school to work and very low levels of education and training. In terms of education levels, a significant proportion of young people (especially in rural areas) leave school early, in part due to what are perceived to be low returns on education. Many of those who do receive high quality education and training choose to emigrate. In a country where more than half the population is under the age of 20 years, these trends are worrisome. Overall, young workers are employed in jobs of low quality and high levels of informality. Female youth are also much more likely to be self-employed (46 percent, versus 32 percent for male youth). More than half of young workers are engaged in agriculture, which predominates in rural areas (82 percent, versus 16 percent in urban areas), and the services sector is the most important source of youth employment in cities and towns, accounting for almost 65 percent of employed youth. Female youth are less likely to be employed or in education, and more likely to be inactive (31 percent, against 27 percent for male youth); possibly reflecting the period when child-rearing and domestic responsibilities begin for female youth. The study assessed the impact of the following factors on youth's time use: education level, gender, local labor supply and demand, and place of residence. From the analysis, it was noted that the probability of being employed decreases as the level of human capital increases. In fact, uneducated youth display the highest probability of being employed.